The chemical composition and toxic effects of aqueous extracts of Cyclocarya paliurus leaves - Liu, Cencen; Zhao, Mouming; Wen, Lingrong; Zhao, Hongwei (Frontiers in Nutrition, 2022)
Cyclocarya paliurus leaves, which possess various bioactivities has been widely used in dietary supplements or ingredient in functional foods. However, limited information is available about the toxicity or safety concerns. In the present work, the maximum tolerated dose (MTD) and potential toxicity of the aqueous extracts of C. paliurus leaves (AECPL) were evaluated. Our results indicated that AECPL was rich in phenolics, flavonoids and polysaccharides, which might be responsible for the health benefits of C. paliurus leaves. The MTD of AECPL was considered to be > 10,000 mg/kg in both male and female rats. The acute toxicity study was carried out by a 14-day repeat dose oral toxicity study. The results showed that the rats were all well tolerated. No treatment-related mortality, abnormal clinical signs, body weight or food consumption changes were reported during the study. Moreover, AECPL showed no adverse changes in the hematology, serum chemistry, urinalysis parameters, organ weights, gross finding and histopathology. In this study, the non-observed-adverse-effect level of AECPL was 5000 mg/kg BW/day, indicating AECPL was safe and can be used in food industry.